Donor-Derived Regulatory Dendritic Cell Infusion Maintains Donor-Reactive CD4+CTLA4hi T Cells in Non-Human Primate Renal Allograft Recipients Treated with CD28 Co-Stimulation Blockade - Ezzelarab, Mohamed B.; Lu, Lien; Shufesky, William F.; Morelli, Adrian E.; Thomson, Angus W. (Frontiers in Immunology, 2018)
Donor-derived regulatory dendritic cell (DCreg) infusion before transplantation, significantly prolongs renal allograft survival in nonhuman primates. This is associated with enhanced expression of the immunoregulatory molecules cytotoxic T-lymphocyte-associated antigen (Ag) 4 (CTLA4) and programmed cell death protein 1 (PD1) by host donor-reactive T cells. In rodents and humans, CD28 costimulatory pathway blockade with the fusion protein CTLA4Ig is associated with reduced differentiation and development of regulatory T cells (Treg). We hypothesized that upregulation of CTLA4 by donor-reactive CD4+T cells in DCreg-infused recipients, treated with CTLA4Ig, might be associated with higher incidences of donor-reactive CD4+T cells with a Treg phenotype. In normal rhesus monkeys, allo-stimulated CD4+CTLA4hi, but not CD4+CTLA4med/lo T cells exhibited a regulatory phenotype, irrespective of PD1 expression. CTLA4Ig significantly reduced the incidence of CD4+CTLA4hi, but not CD4+CTLA4med/lo T cells following allo-stimulation, associated with a significant reduction in the CD4+CTLA4hi/CD4+CTLA4med/lo T cell ratio. In CTLA4Ig-treated renal allograft recipient monkeys, there was a marked reduction in circulating donor-reactive CD4+CTLA4hi T cells. By contrast, in CTLA4Ig-treated monkeys with DCreg infusion, no such reduction was observed. In parallel, the donor-reactive CD4+CTLA4hi/CD4+CTLA4med/lo T cell ratio was reduced significantly in graft recipients without DCreg infusion, but increased in those given DCreg. These observations suggest that pre-transplant DCreg infusion promotes and maintains donor-reactive CD4+CTLA4hi T cells with a regulatory phenotype after transplantation, even in the presence of CD28 costimulation blockade.